English workshop benefits DLP students - Noor Azlinda, Zainal Abidin (2019)
The Centre for Modern Languages & Human Sciences (CMLHS), together with Department of Academic and International conducted the Dual Language Programme (DLP) enrichment workshop for 43 secondary school students on January 2, 2019.